VD_FINDINFO Arrêt / 2011 / 543 vom 3. Mai 2011 - VD Tribunal cantonal (2011)
RENTE POUR ENFANT, DÉBUT, DEMANDE DE PRESTATION D'ASSURANCE, OBLIGATION D'ANNONCER | 35 al. 1 LAI, 24 al. 1 LPGA, 29 LPGA, 65 al. 1 RAI